'RS' and 'GIS' based air quality atlas with integrated land use and land cover change analysis in India. Issue 3 (11th February 2021) - Navalgund, Lokeshwari; Joshi, Keshava; Srinikethan, Govindan; Shet, Vinayaka B; Hosamane, Satish N
Abstract : In this paper, the effect of land use and land cover and the impact of urbanisation on respirable particulate matter (RSPM), sulfur oxide (SO x ) and nitrogen oxide (NO x ) of the Hubli-Dharwad, a Tier II city in India, are correlated based on the trends in air quality observed from 2006 to 2013, population from 1990 to 2010, the number of vehicles between the periods of 2004 and 2013 and urbanisation between the periods of 1975 and 2009. It has been found that urbanisation has increased threefold from 92 km 2 in 1975 to 271 km 2 in 2009 and the corresponding decrease in agricultural area was from 368.22 to 123.43 km 2 . The RSPM in the study region is increasing at a rate of 8.9% per year. The study shows that vehicular pollutants are the major cause of air pollution, followed by industries, with the highest RSPM value of 128 μg/m 3 at traffic junctions in the Hubli-Dharwad region in 2013. Based on the trend analysis, the air quality atlas predicted for 2030 shows that the RSPM level in the air will reach 150 μg/m 3, well above the national ambient air quality standards, and will have serious consequences on human health if proper strategies are not undertaken. Owing to the unique geographical setting of Hubli-Dharwad, its future urbanisation will be in a narrow area, which may lead to a severe air pollution problem that needs immediate attention to provide a safe environment.